Ecology and water quality parameters of Balla beel in Moulovibazar district of Bangladesh - Flura, M; Alam, Mohammad Ashraful; Rahman, Md Anisur; Ahmed, Tayfa; Roy, Krishna Chandra (Asian Journal of Medical and Biological Research, 2015)
A study was carried out to assess the ecological aspects of Balla beel ecosystem in Moulavibazar district and the affectivity of the ongoing biodiversity restoration program from July 2011 to June 2012. Seventy-four fish species belonging to 21 families were identified during the study period. About nine types of fishing methods and one type of fish aggregating device were identified in the surveyed beel. Increasing pressure of illegal current jal (gill net), ber jal (seine net) and FAD (Fish Aggregating Device) was detected as the reduction of almost all type of species. About 24 aquatic weeds were found in the Balla beel, among them both emergent and spreading were 29%, followed by floating 21%, 13% were rooted plants with floating leaves and 8% were submerged. The dissolved oxygen content 5.22±1.60 mg/l inside and 5.70±1.38 mg/l outside of the Balla beel sanctuary were found to be congenial for aquatic life. pH of the beel water both inside and outside of the sanctuary were slightly acidic to moderately alkaline (7.0±0.68 inside and 6.88±0.43 outside the sanctuary). Lower values of alkalinity and hardness indicating beel water to be less nutrient enriched. The contribution of phytoplankton (79%) was larger than zooplankton (21%). The diversity of phytoplankton both inside and outside of the sanctuary was dominated by three group Chlorophyceae, Myxophyceae and Bacillariophyceae. Asian J. Med. Biol. Res. June 2015, 1(2): 198-208